2006
DOI: 10.1111/j.1096-3642.2006.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Dyrosaurus (Crocodylomorpha, Dyrosauridae) from the early Eocene of Morocco: phylogenetic implications

Abstract: A new dyrosaurid is described from the Ypresian of the phosphatic deposits of the Oulad Abdoun Basin of Morocco. It is based on numerous cranial and postcranial remains, allowing an almost complete reconstruction. This new Dyrosaurus species, Dyrosaurus maghribensis sp. nov. , is currently only known from Morocco. It differs from D. phosphaticus , present in contemporaneous levels of Algeria and Tunisia, by several autapomorpies, including a smooth dorsal margin of the parietal and widely opened choanae. A phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
160
4
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(185 citation statements)
references
References 53 publications
9
160
4
3
Order By: Relevance
“…The alveolar edges of d4 are higher than the edges of the other alveoli. The d7 alveoli are reduced and close to the eighth alveoli border as described for D. maghribensis (OCP DEK-GE 253) (Jouve et al, 2006) and C. improcerus (UF/IGM 29) (Hastings et al, 2010); this pattern was also found in an unidentified dyrosaurid, VPL/JU/IR/400, from Maastrichtian strata in India (Khosla et al, 2009). The tenth alveolus is not preserved on the right side of the dentary.…”
Section: Description and Comparisonmentioning
confidence: 77%
See 4 more Smart Citations
“…The alveolar edges of d4 are higher than the edges of the other alveoli. The d7 alveoli are reduced and close to the eighth alveoli border as described for D. maghribensis (OCP DEK-GE 253) (Jouve et al, 2006) and C. improcerus (UF/IGM 29) (Hastings et al, 2010); this pattern was also found in an unidentified dyrosaurid, VPL/JU/IR/400, from Maastrichtian strata in India (Khosla et al, 2009). The tenth alveolus is not preserved on the right side of the dentary.…”
Section: Description and Comparisonmentioning
confidence: 77%
“…The first tooth is oriented anterodorsally and the largest teeth are located at positions d1 and d4. Likewise, the d4 tooth is the largest in Dyrosaurus phosphaticus Thomas, 1893 (MNHN ALG 3 and MNHN APH 27) (Jouve, 2005) and in Dyrosaurus maghribensis Jouve, Iarochène, Bouya & Amaghzaz, 2006 (OCP DEK-GE 253), (Jouve et al, 2006). The alveolar edges of d4 are higher than the edges of the other alveoli.…”
Section: Description and Comparisonmentioning
confidence: 99%
See 3 more Smart Citations